Tidal volume significantly affects oxygenation in healthy pigs during high-frequency oscillatory ventilation compared to conventional ventilation - Roubík, Karel; Ráfl, Jakub; Rožánek, Martin; Kudrna, Petr; Mlček, Mikuláš (Biomedical engineering online, 2022)
BACKGROUND: The role of high-frequency oscillatory ventilation (HFOV) has long been debated. Numerous studies documented its benefits, whereas several more recent studies did not prove superiority of HFOV over protective conventional mechanical ventilation (CV). One of the accepted explanations is that CV and HFOV act differently, including gas exchange. METHODS: To investigate a different level of coupling or decoupling between oxygenation and carbon dioxide elimination during CV and HFOV, we conducted a prospective crossover animal study in 11 healthy pigs. In each animal, we found a normocapnic tidal volume (VT) after the lung recruitment maneuver. Then, VT was repeatedly changed over a wide range while keeping constant the levels of PEEP during CV and mean airway pressure during HFOV. Arterial partial pressures of oxygen (PaO2) and carbon dioxide (PaCO2) were recorded. The same procedure was repeated for CV and HFOV in random order. RESULTS: Changes in PaCO2 intentionally induced by adjustment of VT affected oxygenation more significantly during HFOV than during CV. Increasing VT above its normocapnic value during HFOV caused a significant improvement in oxygenation, whereas improvement in oxygenation during CV hyperventilation was limited. Any decrease in VT during HFOV caused a rapid worsening of oxygenation compared to CV. CONCLUSION: A change in PaCO2 induced by the manipulation of tidal volume inevitably brings with it a change in oxygenation, while this effect on oxygenation is significantly greater in HFOV compared to CV.
Keywords: Tidal Volume; Animals; plíce; Tidal volume; Oxygenation; zvířata; prospektivní studie; dechový objem; Lung; Mechanical ventilation; Pulmonary Gas Exchange; prasata; výměna plynů v plicích; vysokofrekvenční ventilace; Prospective Studies; Swine; High-frequency oscillatory ventilation; High-Frequency Ventilation